MENUMBUHKAN KEMBALI MINAT BELAJAR SEJARAH LOKAL PELABUHAN SENAPELAN PADA DIRI SISWA SMA MELALUI KARYA WISATA - Aisyah Nur Hanifah (Jurnal Pendidikan Sejarah Indonesia, 2021)
The introduction of the Senapelan Harbor, as a part of history of the early birth of the city of Pekanbaru, to students is very important as part of a local history. To explore the historical story and the existence of Senapelan Harbor in the present, it is important for History teachers to introduce the port site through the field work learning method, accompanied by an android-based digital map media. The purposes of this study are (1) to determine how much knowledge high school students in Pekanbaru have about the historical sites of Senapelan Harbor. (2) to determine the effectiveness of the field trip method and digital maps in fostering the love of high school students for the local history of Senapelan Harbor. (3) to find out how much student achievement in learning local history has increased, by using the historical tourism work research method, based on digital maps.